2021
DOI: 10.1186/s43094-021-00264-w
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological uses, phytochemistry, pharmacology, and toxicology of Olax subscorpioidea Oliv (Olacaceae): a review

Abstract: Background The plant Olax subscorpioidea Oliv (Olacaceae) is a shrub that is widely available in Africa. It has been used in traditional medicine to treat various diseases including asthma, pain, inflammation, gastrointestinal and central nervous system (CNS) disorders, cough, diabetes mellitus, cancer, infectious diseases, hepatic diseases, and many other diseases. Several phytochemical and pharmacological investigations were conducted on this plant. However, comprehensive information on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Many medicinal plants show potential in fighting cancer, but few have been fully researched. One example is O. subscorpioidea a member of Olacaceae (12). Although the plant is known for its antioxidant and anticancer effects, its bioactive components and mechanisms of action are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many medicinal plants show potential in fighting cancer, but few have been fully researched. One example is O. subscorpioidea a member of Olacaceae (12). Although the plant is known for its antioxidant and anticancer effects, its bioactive components and mechanisms of action are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Olax subscorpioidea, a member of the Olacaceae, is one. This plant is common in Africa and has been used to address various health concerns, including asthma, inflammation, cough, infectious diseases, diabetes, hepatitis, and cancer (12). Popoola et al found that the herb may prevent and cure cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…In pharmacological research, it was found that Olax subscorpioidea fractions and extracts exhibited analgesic, anti-inflammatory, antibacterial, antidiabetic, antimalarial, and antioxidant properties. 16 Unfortunately, there is still a limited understanding of the breast cancer anticancer mechanisms of Olax subscorpioidea. Thus, the study evaluated the anticancer properties of the ethyl acetate fraction and ethanol leaf extract of Olax subscorpioidea can help fight cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Hexane, ethyl acetate and acetone fractions of leaf extract of Olax subscorpioidea were reported to show remarkable inhibition of α-amylase and α-glucosidase which are the carbohydrate digesting enzymes. [16] There are many reports available on various species of genus Olax for their antihyperglycemic activity but similar reports on O. scandens are not available and scientifically not evaluated. To provide scientific evidence to traditional claim of O. scandens bark being used as a supporting drug to treat diabetes.…”
Section: Introductionmentioning
confidence: 99%